2016
DOI: 10.1177/0145721716666679
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Adaptation of the Group Lifestyle Balance Program for Chinese Americans

Abstract: Results suggest that the culturally adapted Group Lifestyle Balance program for Chinese Americans was both acceptable and effective. The culturally adapted program warrants further examination using scientific approaches for dissemination and implementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 41 publications
3
10
0
Order By: Relevance
“…The results of this study demonstrated high feasibility and acceptability of this intervention. The retention rate was comparable to or better than that previously reported in in-person diabetes interventions in Chinese immigrants [ 8 , 9 , 38 ]. The video watch rate was high over the 12-week intervention, with an adherence rate higher than most in-person DSME interventions in Chinese immigrants [ 6 , 8 , 9 , 38 ].…”
Section: Discussionsupporting
confidence: 77%
“…The results of this study demonstrated high feasibility and acceptability of this intervention. The retention rate was comparable to or better than that previously reported in in-person diabetes interventions in Chinese immigrants [ 8 , 9 , 38 ]. The video watch rate was high over the 12-week intervention, with an adherence rate higher than most in-person DSME interventions in Chinese immigrants [ 6 , 8 , 9 , 38 ].…”
Section: Discussionsupporting
confidence: 77%
“…Funded sites frequently implemented cultural adaptations to address participants’ needs or preferences, which were positively associated with participants’ overall attendance, attendance in months 7–12, and duration of participation. This finding is consistent with Chesla et al, who adapted the CDC-approved Group Lifestyle Balance curriculum for Chinese Americans with prediabetes, resulting in greater achievement of the 5% weight loss goal when compared to Chinese Americans receiving a non-adapted curriculum [42]. We did not, however, find improved results among sites that used language adaptations.…”
Section: Discussionsupporting
confidence: 91%
“…All eight studies conducted among children/adolescents were conducted in San Francisco, CA, USA [26][27][28][29][30][34][35][36], and all but one [26] were led by the same principal investigator (Chen) ( Table 1). Among adults, one study was set in Australia [37], one in Canada [33], and one in South Korea [38], while all others were conducted in the United States [31,32,[39][40][41][42][43][44][45][46][47] (Table 2). The average sample size was 60 and 63 among studies conducted in children/adolescents and adults, respectively (Tables 1 and 2).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Among adults, three studies were randomized controlled trials, nine studies were pre-post single-arm interventions, and two studies were two-group repeated measures quasi-experimental design (Table 4). Interventions included adaptations of the Diabetes Prevention Program [32,37,39,45] DASH diet [33], a cancer survival program [41], diabetes management programs [43,46,47], walking programs [38,40], community-based programs [42], tai chi [44], and an intervention to incorporate more brown rice in the diet [31]. Theoretical models included Transtheoretical Model, Culture Care Theory, Chronic Care model, Theory of reasoned action, Orem's theory of self care, Empowerment model, RE-AIM, Social Cognitive Theory, and traditional Chinese Medicine principles (Table 4).…”
Section: Intervention Characteristicsmentioning
confidence: 99%